2017
DOI: 10.1016/j.compstruct.2016.10.121
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics and band gaps in hierarchical auxetic rectangular perforated composite metamaterials

Abstract: We describe in this work a composite metamaterial with a hierarchical topology made by tessellating perforations that exhibit an auxetic (negative Poisson's ratio) behaviour. We perform an analysis of the hierarchical structure by evaluating the fractal order of the topologies associated to the perforared composites.The periodic hierarchical lattice configuration shows negative Poisson's ratio characteristics at higher levels of hierarchy, even when the baseline configuration has a topology not exhibiting an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 43 publications
0
52
0
Order By: Relevance
“…[16][17][18][19] Interestingly, it has also been shown that the introduction of hierarchy into kirigami structures further enrich their functionality as it enables higher stretchability, [20,21] wider tunability of the bandgaps, [21][22][23] and larger negative Poisson's ratios. [16][17][18][19] Interestingly, it has also been shown that the introduction of hierarchy into kirigami structures further enrich their functionality as it enables higher stretchability, [20,21] wider tunability of the bandgaps, [21][22][23] and larger negative Poisson's ratios.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18][19] Interestingly, it has also been shown that the introduction of hierarchy into kirigami structures further enrich their functionality as it enables higher stretchability, [20,21] wider tunability of the bandgaps, [21][22][23] and larger negative Poisson's ratios. [16][17][18][19] Interestingly, it has also been shown that the introduction of hierarchy into kirigami structures further enrich their functionality as it enables higher stretchability, [20,21] wider tunability of the bandgaps, [21][22][23] and larger negative Poisson's ratios.…”
mentioning
confidence: 99%
“…[16][17][18][19] Interestingly, it has also been shown that the introduction of hierarchy into kirigami structures further enrich their functionality as it enables higher stretchability, [20,21] wider tunability of the bandgaps, [21][22][23] and larger negative Poisson's ratios. [20][21][22][23][24][25] The out-of-plane buckling behavior of thin hierarchical kirigami sheets remains largely unexplored, and the only closely related study focuses on a system in which patterned notches are introduced in addition to cuts to guide the pop-up in a preferred direction. [20][21][22][23][24][25] The out-of-plane buckling behavior of thin hierarchical kirigami sheets remains largely unexplored, and the only closely related study focuses on a system in which patterned notches are introduced in addition to cuts to guide the pop-up in a preferred direction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical metamaterials have been recently hailed as a new class of structural concept able to bring novel multifunctionalities 4 by changes of compliance, shape, or by embedding oscillators or smart material inserts. Some examples (to name a few) are multiscale architecturally structured topologies, 5 zig-zag folded sheets, 6 pentamodal lattices, 7 systems with distributed resonators, 8,9 smart/magnetic materials, 10 tunable connectivity, 11 phononic stubbed plates, 12 flat lenses (super lenses), 13 3D tunable phononic crystals, 14 tunable metamaterial beam with shape memory alloy resonators, 15,16 auxetic periodic structure (with negative Poisson ratio) 17,18 and nonlinear auxetic dampers. 19 Further author information: (Send correspondence to Morvan Ouisse) E-mail: morvan.ouisse@femto-st.fr, Telephone: +33 3 81 66 60 00 A phononic crystal is a metamaterial with a periodic structure, that exhibits spatial periodicity.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al have studied the bandgap structures of a periodic beam lattice activated via local resonance of the beam elements . Recent works have investigated the wave propagation behaviors in hierarchical structures, and found that both Bragg bandgaps and local resonance bandgaps exist in the hierarchical structures. However, few works have been performed to study the bandgaps of hierarchical auxetic structures …”
Section: Introductionmentioning
confidence: 99%